The Gateway to Computer Science Excellence
+2 votes
Using Armstrong’s axioms of functional dependency derive the following rules:

$\{ x \rightarrow y, \: wy \rightarrow z \} \mid= xw \rightarrow z$

(Note: $x \rightarrow y$ denotes $y$ is functionally dependent on $x$, $z \subseteq y$ denotes $z$ is subset of $y$, and $\mid =$ means derives).
in Databases by | 211 views

1 Answer

+4 votes
Best answer
$x \rightarrow y$ (Given)

$\implies xw \rightarrow yw$ ( using axiom of augmentation $A \rightarrow B$ $\implies AX \rightarrow BX$)

also $yw \rightarrow z$ (Given)

$\implies xw \rightarrow z$ (using Axiom of transitivity ($A \rightarrow B$ and $B \rightarrow C)$ $\implies A \rightarrow C$)
selected by

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
52,345 questions
60,506 answers
95,345 users